Change of Hemoglobin Levels in the Early Post-cardiac Arrest Phase Is Associated With Outcome - Schriefl, Christoph; Schoergenhofer, Christian; Ettl, Florian; Poppe, Michael; Clodi, Christian; Mueller, Matthias; Grafeneder, Juergen; Jilma, Bernd; Magnet, Ingrid Anna Maria; Buchtele, Nina; Boegl, Magdalena Sophie; Holzer, Michael; et al. (Frontiers in Medicine, 2021)
Background: The post-cardiac arrest (CA) phase is characterized by high fluid requirements, endothelial activation and increased vascular permeability. Erythrocytes are large cells and may not leave circulation despite massive capillary leak. We hypothesized that dynamic changes in hemoglobin concentrations may reflect the degree of vascular permeability and may be associated with neurologic function after CA. Methods: We included patients ≥18 years, who suffered a non-traumatic CA between 2013 and 2018 from the prospective Vienna Clinical Cardiac Arrest Registry. Patients without return of spontaneous circulation (ROSC), with extracorporeal life support, with any form of bleeding, undergoing surgery, receiving transfusions, without targeted temperature management or with incomplete datasets for multivariable analysis were excluded. The primary outcome was neurologic function at day 30 assessed by the Cerebral Performance Category scale. Differences of hemoglobin concentrations at admission and 12 h after ROSC were calculated and associations with neurologic function were investigated by uni- and multivariable logistic regression. Results: Two hundred and seventy-five patients were eligible for analysis of which 143 (52%) had poor neurologic function. For every g/dl increase in hemoglobin from admission to 12 h the odds of poor neurologic function increased by 26% (crude OR 1.26, 1.07–1.49, p = 0.006). The effect remained unchanged after adjustment for fluid balance and traditional prognostication markers (adjusted OR 1.27, 1.05–1.54, p = 0.014). Conclusion: Increasing hemoglobin levels in spite of a positive fluid balance may serve as a surrogate parameter of vascular permeability and are associated with poor neurologic function in the early post-cardiac arrest period.